Aptasensor for the detection of Methicillin resistant Staphylococcus aureus on contaminated surfaces - Raji, Muhabat Adeola; Suaifan, Ghadeer; Shibl, Atef; Weber, Karina; Cialla-May, Dana; Popp, Jürgen; Al-Kattan, Khaled; Zourob, Mohammed (Biosensors and Bioelectronics, 2021)
There is mounting evidence that contaminated hospital environment plays a crucial role in the transmission of nosocomial pathogens such as MRSA. The institution of infection control protocols is predicated on the early laboratory detection of the pathogen from relevant samples. Processing of environmental samples for the presence of bacterial contaminants in the clinical environment is poorly standardized when compared with analysis of clinical samples. The various laboratory methods available for processing environmental samples are difficult to standardized and most require a long turnaround time before results are available. In this study, we present a report of the performance of a novel pathogen aptasensor swab designed to qualitatively and quantitatively detect MRSA, on contaminated non-absorbable surfaces. The visual detection limit of the MRSA aptasensor swab was less than 100 CFU/ml and theoretically using a standard curve, was 2 CFU/ml. A relatively short turnaround time of 5 min was established for the assay while the linear range of quantitation was 102–105 CFU/ml. Engineered aptasensor targets MRSA selectively and binds to none of the other tested bacterial pathogen, on a multi-contaminated surface. This novel detection tool was easy to use and relatively cheap to produce.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Aptasensor; Environmental contamination; Hospital environment; MRSA